The FRIENDS preventive programme for reducing anxiety symptoms in children and adolescents: A systematic review and meta‐analysis - Trine Filges; Geir Smedslund; Tine Eriksen; Kirsten Birkefoss; Malene Wallach Kildemoes (Campbell Systematic Reviews)
Abstract Background Anxiety and stress responses are often considered normative experiences, and children and adolescents may benefit from anxiety prevention programmes. One such programme is FRIENDS which is based on a firm theoretical model which addresses cognitive, physiological and behavioural processes. FRIENDS is manualised and can, thus, easily be integrated into school curriculums. Objectives What are the effects of the FRIENDS preventive programme on anxiety symptoms in children and adolescents? Do the effects differ between participant age groups, participant socio‐economic status, type of prevention, type of provider, country of implementation and/or implementation issues in relation to the booster sessions and parent sessions? Search Methods The database searches were carried out in September 2023, and other sources were searched in October 2023. We searched to identify both published and unpublished literature. A date restriction from 1998 and onwards was applied. Selection Criteria The intervention was three age‐appropriate preventive anxiety programmes: Fun FRIENDS, FRIENDS for Life, and My FRIENDS Youth. Primary outcome was anxiety symptoms and secondary outcome was self‐esteem. Studies that used a control group were eligible, whereas qualitative approaches were not. Data Collection and Analysis The number of potentially relevant studies was 2865. Forty‐two studies met the inclusion criteria. Twenty‐eight studies were used in the data synthesis. Four studies had a critical risk of bias. Six studies did not report data that enabled calculation of effect sizes and standard errors. Two studies had partial overlap of data to other studies used, and two were written in Persian. Meta‐analyses were conducted on each outcome separately. All analyses were inverse variance weighted using random effects statistical models. Main Results Studies came from 15 different countries. Intervention start varied from 2001 to 2016. The average number of participants analysed was 240, and the average number of controls was 212. Twenty‐five comparisons reported on anxiety symptoms post‐intervention. The weighted average standardised mean difference (SMD) was 0.13 (95% CI 0.04 to 0.22). There was some heterogeneity. Twelve comparisons reported on anxiety symptoms at 12 months follow‐up. The weighted average SMD was 0.31 (95% CI 0.13 to 0.49). There was a large amount of heterogeneity. Five comparisons reported on self‐esteem post‐intervention with a weighted average SMD of 0.20 (95% CI −0.20 to 0.61) and a large amount of heterogeneity. At follow‐up, we found evidence that programmes implemented by mental health providers appears to perform better than programmes implemented by teachers. The evidence was inconclusive beyond 12 months follow‐up. Authors' Conclusions Our results indicate that the FRIENDS intervention may reduce anxiety symptoms in children and adolescents when reported by children and adolescents themselves. The majority of trials employed a wait‐list design, implying only a few studies reported on the long‐term effects of the FRIENDS intervention. Our findings suggest that the FRIENDS intervention may increase the reduction in anxiety symptoms 12 months after the intervention. This emphasises the need for future research that apply designs that allows for long‐term follow‐up. We are uncertain about the effects on self‐esteem. The overall certainty of evidence varied from low to very low. There is a need for more rigorously conducted studies.